Using ChatGPT to Help Make Hots Questions Quickly and Easily - Maiyanti, Aziza Anggi; Yusal, Yulianti; Anggraini, Atika (Proceeding International Conference on Education, 2023)
ChatGPT Open AI is an artificial intelligence-based machine technology that is trained to be able to mimic human conversation using NLP (Natural Language Processing) technology. In fact, ChatGPT can be used to produce questions with good and effective techniques. Therefore, the opportunity to use this technology is wide open for education in Indonesia, one of which is in helping to make HOTS (high order thinking skills) questions quickly and easily for teachers to practice 21st century skills. These skills include critical thinking skills, creative thinking skills, collaboration, and communicative skills. The research method used is in the form of an experiment using a laptop with 4 GB of RAM connected to an internet network and a ChatGPT account which can be created for free at https://chat.openai.com. The results of experiments carried out using ChatGPT can produce HOTS questions in the amount of 5 multiple choice questions complete with discussion on optical material that still needed further examination. The total time needed to complete this experiment is approximately 3 minutes, including the time to document the ChatGPT processing results.